Digitalisasi Kepercayaan: Rekonfigurasi Jaringan Sosial Nelayan Dan Modal Sosial Baru Dalam Sistem Blockchain Di Kabupaten Sumenep - Faizuddin, Iqbal Mahfudz; Wardhana, Indra Jaya Kusuma; Prananta, Arie Wahyu (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2025)
Digital transformation in the fisheries sector has brought fundamental changes to the social relations and trust systems among fishermen. This study aims to understand how digitalization through blockchain technology reconfigures social networks and shapes new forms of social capital among fishermen in Sumenep Regency. Using a phenomenological approach, this research explores fishermen’s subjective experiences in adapting to digital systems that demand transparency, accountability, and technology-based trust. Grounded in Robert Putnam’s social capital theory, the findings reveal that blockchain implementation not only enhances economic efficiency but also creates a new social arena that fosters digital trust and hybrid social networks between humans and systems. Traditional trust, previously built through patronage and informal relations, is transforming into a systemic form of trust governed by algorithmic mechanisms. This process generates digital social capital that extends fishermen’s networks beyond local communities, yet also produces ambivalence toward the erosion of traditional collective values. Thus, the digitalization of trust through blockchain represents a complex sociotechnical process that reshapes social structures and the collective identity of coastal communities.